Against all odds : my story - Norris, Chuck, 1940- (Nashville, Tennessee : Broadman & Holman Publishers, 2004)
The martial arts champion and popular actor traces his life, including his difficult childhood, his discovery of the martial arts and their impact on his life, his successful acting career, and his work teaching martial arts to at-risk youth.
Keywords: Norris, Chuck, -- 1940-; Martial artists -- United States -- Biography; Actors -- United States -- Biography; Norris, Chuck, -- 1940-; Actors; Martial artists; Martial artists -- Biography; Actors -- United States -- Biography; Actors -- United States -- Biography; Biography